2022
DOI: 10.1021/acs.inorgchem.2c01053
|View full text |Cite
|
Sign up to set email alerts
|

Gate Opening without Volume Change Triggers Cooperative Gas Interactions, Underpins an Isotherm Step in Metal–Organic Frameworks

Abstract: Three halogenated metal–organic frameworks (MOFs) reported recently exhibited a second step in their CO2 gas adsorption isotherms. The emergence of halogen-bonding interactions beyond a threshold gas pressure between the framework halogen and the CO2 guest was conjectured to be the underlying reason for the additional step in the isotherm. Our investigation employing periodic density functional theory calculations did not show significant interactions between the halogen and CO2 molecules. Further, using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…It is likely that a more accurate description of the halogen atom is needed, taking into account that the electron density is modified by surrounding atoms, breaking the symmetry so that the negative ring splits into regions of more or less negative charge. 48 , 49 , 50 We also performed free-energy perturbation calculations of the relative binding affinities of the five ligands and showed that the standard parameters reproduced the experimental binding affinities excellently (within 1.8 kJ/mol), whereas the EP parameters gave much worse results ( cf . Table S3 ).…”
Section: Resultsmentioning
confidence: 95%
“…It is likely that a more accurate description of the halogen atom is needed, taking into account that the electron density is modified by surrounding atoms, breaking the symmetry so that the negative ring splits into regions of more or less negative charge. 48 , 49 , 50 We also performed free-energy perturbation calculations of the relative binding affinities of the five ligands and showed that the standard parameters reproduced the experimental binding affinities excellently (within 1.8 kJ/mol), whereas the EP parameters gave much worse results ( cf . Table S3 ).…”
Section: Resultsmentioning
confidence: 95%
“…55 This geometry-based criterion for halogen bonding identication is a necessary condition but not a sufficient one, especially for the case of guests conned within MOF/ PCP pores. 56 The electronic structure, however, denitively reveals the presence of such interactions. Hence, to elucidate this specic interaction (blue-dashed line in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, to elucidate this specific interaction (blue-dashed line in Fig. 4a), we have calculated maximally localized Wannier functions (MLWFs), and their corresponding centers – maximally localised Wannier function centers (MLWFCs), 56–58 MLWFs (violet surfaces) and MLWFCs (yellow spheres) of CO1 (Fig. 4g–h) show that the π-electrons of the double bond face the C–Cl axis.…”
Section: Resultsmentioning
confidence: 99%
“…Given the differences in the functionalisation of the ligands, we speculate that there may be enhanced interactions between CO 2 molecules and the bromo‐functionalised ligand of 3 a in comparison to the cages 1 a and 2 a . Halogen bonding interactions with CO 2 have been proposed as leading to pseudo‐gate opening behaviour in MOFs, [20] but the role of those interactions is contested [21] . The lack of structural information for MOPs in their activated state is common in the field, and represents a challenge for understanding their structure‐property relationships, particularly with gas sorption behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Given the differences in the functionalisation of the ligands, we speculate that there may be enhanced interactions between CO 2 molecules and the bromo-functionalised ligand of 3 a in comparison to the cages 1 a and 2 a. Halogen bonding interactions with CO 2 have been proposed as leading to Chemistry-A European Journal pseudo-gate opening behaviour in MOFs, [20] but the role of those interactions is contested. [21] The lack of structural information for MOPs in their activated state is common in the field, and represents a challenge for understanding their structure-property relationships, particularly with gas sorption behaviour. The post-sorption analysis of 1 a, 2 a, and 3 a using IR spectroscopy and PXRD showed that the materials retain the packing associated with the MeOH solvate phases 1-MeOH, 2-MeOH, and 3-MeOH, suggesting that the materials do not decompose under activation (Figures S33-S38), although there is an appreciable loss in crystallinity.…”
Section: Gas Sorption Measurementsmentioning
confidence: 99%